Grundtvigs indflydelse på den tidlige danske nationalisme - Rerup, Lorenz (Grundtvig-studier, 1992)
Grundtvig’s Position in Early Danish Nationalism By Lorenz Rerup The article deals with Grundtvig’s important position in Early Danish nationalism, i.e., in the decades from about 1800 to 1830. The background is the Danish Monarchy from the prosperous years at the turn of the century to the disastrous war 1807-1814, the loss of Norway in 1814, and the following needy postwar time. After 1814 the Danish Monarchy consisted of the Kingdom of Denmark, the Duchies of Schleswig and Holstein, the North-Atlantic Islands (the Faeroes and Greenland) and some minor colonies. The ideology which integrated the higher ranks of these heterogeneous ethnic groups of the Monarchy into one society was a patriotism underlining peace and order in the realm, the importance of just government and - before 1807 - the protection provided by the Danish navy.The patriotism of the Monarchy was compatible with various feelings of identity which bred in different parts of it from about 1750. The Danes, living in an old kingdom, equipped with a written language, with a complete educational system, and with a history of their own, of course, had a feeling of a Danish identiy, as the German speaking population of the Duchies had a corresponding feeling of an identity of their own. Clashes of these different identities might happen but were not connected with political ideas. The state was run by the king, not by the people, and a public opinion about politics was not allowed - and was almost non-existent - before the announcement of the Advisory Estates Assemblies in 1831. Now nationalism spread and soon undermined the supranational Monarchy, which finally disintegrated in 1864.However, in the first decades of the 18th century and influenced by the ideas of Romanticism a few poets, first of all Grundtvig, developed a literary national movement without political aims. In the writings of these poets the Danes - the whole people - have a real chance to make history if they abandon their superficial life and revive the virtues and piety of the great periods in Danish history. Like political nationalists these poets propagate this kind of revival. Their attempt failed. People were still divided into a ’high’ and a ’broad’ culture and some decades had to pass until the latter one felt the need of an ideology in order to be integrated into society. Nevertheless, Grundtvig seems to be a kind of link between the patriotic ideology of the 18th and the political nationalism of the 19th century.